Safety Evaluation and Flow Modification in the Anterior Cerebral Artery after Pipeline Embolization Device Deployment across the Internal Carotid Artery Terminus. (23rd August 2021) - Xu, Chao; Wu, Pei; Han, Jianyi; Sun, Bowen; Wang, Chunlei; Xu, Shancai; Luo, Bin; Yang, Xinjian; Mu, Qingchun; Shi, Huaizhang
Abstract : Background and Objective . Whether anterior cerebral artery occlusion occurs after pipeline embolization devices (PEDs) are implanted to treat posterior communicating artery aneurysm is controversial. The purposes of this study were to explore the effect of a PED covering A1 on patients' clinical prognosis and to evaluate the factors related to vascular occlusion. Method . The clinical and imaging data of PEDs in the postmarket multicenter registry study (PLUS) in China were retrospectively analyzed, and patients were divided into two groups on the basis of the follow-up angiographic results: group 1 (no significant change in A1 blood flow) and group 2 (A1 occlusion or decreased blood flow). We collected patients' baseline data and evaluated the following imaging indicators: diameter and ratio of bilateral A1, M1, and internal carotid artery (ICA) vessels before stenting and the ratio of the PED size (sPED) to the ipsilateral ICA (I-ICA) diameter on the implantation side. Results . A total of 1171 patients were included, of whom 48 met the inclusion criteria (17 in group 1 and 31 in group 2). In group 2, three patients experienced neurological deterioration at follow-up. From the univariate analysis of outcomes, single PED without coils, incomplete aneurysm occlusion (IAO), maximum aneurysm diameter, aneurysms involving the ICA bifurcation (ICAb), and large sPED/I-ICA diameter ratio were included in the multivariate analysis (P < 0.20 ). The multivariate regression analysis results showed that the ratio of sPED/I-ICA diameter was the factor influencing A1 vessel occlusion. The area under the ROC curve was 73.2%. When the sPED/I-ICA diameter ratio was 1.14, sensitivity was 70.6%, and specificity was 77.4%. Conclusion . When an oversized PED is placed from M1 to the ICA, the higher porosity formed at the covered A1 orifice is conducive to maintaining stable A1 blood flow and reducing the risk of A1 vessel occlusion. This trial is registered with ClinicalTrials.gov identifier: NCT03831672 .